The Relationship Between Color Mixing Learning Activities and Fine Motor Skills In Early Childhood - Hidayat, Heri; Muftie, Zenal; Lestari, Indrie Dwi (Bulletin of Early Childhood, 2023)
In the activity of mixing colours and fine motor skills, some children have high enthusiasm and are skilled in using stationery. However, some children still have problems with their fine motor skills. Such as the application of colours to objects that are not yet certain, children are still stiff when using their fingers, and children are still unable to coordinate between the eyes and hands with one activity they do because children are easily distracted by other activities. The purpose of this research is to find out: The reality of learning activities to mix colours in Group B2 RA Al-Muhajir Panyileukan Bandung City, the reality of fine motor skills of early childhood in Group B2 RA Al-Muhajir Panyileukan Bandung City, and the reality of the relationship between learning activities to mix colors with fine motor skills in children in Group B2 RA Al-Muhajir Panyileukan Bandung City. This research method uses a correlation method with a quantitative approach. The samples obtained in this study were 12 children from group B2 RA Al-Muhajir Bandung City. For data collection techniques used by researchers are observation, documentation, and performance techniques. The results of data analysis on the variable learning activity of mixing colours in this study show that the learning activity of mixing colours is in a very good category with a value of 85.70 and fine motor skills of early childhood are in a very good category with a value of 88.05 this figure is in the interval table 80-100. There is a significant relationship between learning activities mixing colours with fine motor skills of early childhood in group B2 RA Al-Muhajir Bandung City, with a very strong / very high level of relationship at the price of the correlation coefficient of 0.85 which is included in the interval 0.80-1.000 Keywords: Color Mixing, Fine Motor Skills, Early Childhood